India's COVID-19 Burdens, 2020 - Joshi, Ashish; Mewani, Apeksha H.; Arora, Srishti; Grover, Ashoo (Frontiers in Public Health, 2021)
The purpose of this article is two-pronged:- firstly to identify and report public health implications of the ongoing coronavirus (COVID-19) pandemic, and secondly to report challenges uniquely faced by the citizens of India from a population health lens, both while closely examining epidemiological data that is accessible via- SMAART’s (Sustainable, Multisector, Accessible, Affordable, Reimbursable, Tailored) RAPID (Research-enabled Action-oriented Policy Interventions driven by Data platform) Tracker. This policy informatics platform is a live database aimed to track the geospatial spread of the COVID-19 outbreak and policy actions globally and administered collaboratively by CUNY’s Graduate School of Public Health and Health Policy and a global, non-profit public health incubator. Infectivity rate, incidence rate, and recovery rate were computed and graphical representations of epidemiological datasets were studied. A plausible conceptual framework is discussed for countries with similar characteristics to build a stronger public and community health foundation to safeguard populations during a future health emergency.